Höhenänderungen im grönländischen Inlandeis zwischen 1959 und 1968. - Seckel, H. (Meddelelser om Grønland, 1977)
The aim of repeated levellings across the icecap of Greenland was to determine the vertical component of the ice movement and the variation of the height of the icecap along a certain profile. The measurement of both campaigns, 1959 und 1968, are compared regarding the ice-movement during the levellings and other superposing influences as well. The results show a slight and asymetric elevation of the icecap.